Effect of 3-week Behavioral Intervention to Reduce Sedentary Behavior on Body Composition and Blood Biomarkers: A Pilot Study (P16-017-19). (13th June 2019) - Huang, Wei-Lin; Dawson, John; Olvera, Hannah; Binks, Martin
Abstract: Objectives: Sedentary behavior has been linked to increased health risks yet few RCTs examine sedentary behavior in the context of meaningful health outcomes. Furthermore, few studies examine scalable interventions. This 3-week pilot study examined if cognitive behavioral sedentary behavior intervention (CBSB) or stress management (CBSM) intervention delivered via the internet (video) had a positive effect on sedentary behavior measured via the Sedentary Behaviour Questionnaire (SBQ) and pedometer. The study further investigated changes in body weight (∆BW), body fat mass (∆BF), fat free mass (∆FFM), total cholesterol (∆TC), triglycerides (∆TG), low-density lipoprotein (∆LDL), high-density lipoprotein (∆HDL), and fasting glucose (∆Glc). Methods: Twenty-one subjects were randomized into one of the 3 groups, control (C), CBSB, or CBSM. All subjects received educational handouts at the first assessment visit. CBSB and CBSM received one group-specific CBT video lesson weekly; C received a neutral video. Daily step count was collected throughout the study via pedometer. Blood lipid panels (TC, TG, LDL, and HDL) and Glc were collected via finger stick at baseline and after the 3-week intervention. The Kruskal-Wallis test was used to compare difference scores (between baseline and post-intervention) across groups. Results: Change in daily step count and SBQ score did not significantly differ across groups ( P  = .767, P  = .796 respectively). No significant group differences were found in ∆TC, ∆TG, ∆LDL, ∆HDL, and ∆Glc ( P  = .478, P  = .499, P  = .675, P  = .536, P  = .062 respectively). ∆BW, ∆BF, and ∆FFM were not significantly different across three groups ( P  = .817, P  = .056, P  = .069 respectively). Adherence to assigned intervention was 100%. Conclusions: It is likely that a 3-week CBT intervention delivered remotely may have been insufficient to induce meaningful behavioral and biological change. However, excellent adherence in this pilot study provides initial proof of concept regarding the acceptability of the intervention and thus the potential for this scalable intervention to be delivered successfully. Larger studies that include health and behavioral outcomes, utilize longer and possibly higher intensity remotely delivered intervention are needed. Funding Sources: Texas Tech University.